And they were wonderful teachers : Florida's purge of gay and lesbian teachers - Graves, Karen, 1959- (Urbana : University of Illinois Press, 2009)
Focusing on Florida's purge of gay and lesbian teachers from 1956 to 1965, this study explores how the Florida Legislative Investigation Committee, commonly known as the Johns Committee, investigated and discharged dozens of teachers on the basis of sexuality. Details how teachers were targeted, interrogated, and stripped of their professional credentials, and examines the extent to which these teachers resisted the invasion of their personal lives. Contrasts the experience of three groups--civil rights activists, gay and lesbian teachers, and University of South Florida personnel--called before the committee and looks at the range of response and resistance to the investigations. Highlights the importance of sexuality in American and education history and argues that Florida's attempt to govern sexuality in schools implies that educators are distinctly positioned to transform dominant ideology in American society. From publisher description.
Politics of intimidation in the Sunshine State -- A stealth investigation -- Silence will not protect you -- Doing the public's business -- A profession at risk.
Includes bibliographical references and index.
The Cushing Library/Women & Gender Studies copy was acquired as part of The Don Kelly Research Collection of Gay Literature and Culture.
Print version record.
eBooks on EBSCOhost
Keywords: Florida. -- Legislature. -- Legislative Investigation Committee; Florida. -- Legislature. -- Legislative Investigation Committee; Gay teachers -- Dismissal of -- Florida -- History -- 20th century; Lesbian teachers -- Dismissal of -- Florida -- History -- 20th century; Discrimination in education -- Florida -- History -- 20th century; Homophobia in high schools -- Florida -- History -- 20th century; Gay teachers -- Dismissal of -- Florida -- History; Lesbian teachers -- Dismissal of -- Florida -- History; Discrimination in education -- Florida -- History; Enseignants homosexuels -- Licenciement -- Floride -- Histoire; Enseignantes lesbiennes -- Licenciement -- Floride -- Histoire; Discrimination en éducation -- Floride -- Histoire; Enseignants homosexuels -- Licenciement -- Floride -- Histoire -- 20e siècle.; Enseignantes lesbiennes -- Licenciement -- Floride -- Histoire -- 20e siècle.; Discrimination en éducation -- Floride -- Histoire -- 20e siècle.; Homophobie dans les écoles -- Floride -- Histoire -- 20e siècle.; EDUCATION / General; Homophobia in high schools; Discrimination in education; Florida; Homosexueller; Entlassung; Lehrerin; Lesbe; Sexuelle Orientierung; Diskriminierung; Lehrer; Florida; Homosexuella -- diskriminering -- Förenta staterna; Lesbiska kvinnor -- diskriminering -- Förenta staterna; History